PENINGKATAN KETERAMPILAN PROSES SAINS SISWA SMP MELALUI PENERAPAN MODEL CREATIVE PROBLEM SOLVING - Sholikhah, Nur; Subekti, Hasan (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
Science Process Skills (SPS) are fundamental competencies that enable students to apply scientific methods to systematically explore scientific phenomena. The development of SPS not only encourages conceptual understanding but also trains observation, analysis, and problem-solving skills. This study aims to test the effectiveness of the Creative Problem Solving (CPS) learning model in improving the SPS of grade VIII students. The method used is a pre-experimental design with a one-group pretest-posttest design, involving 27 grade VIII-B students at a junior high school in Sidoarjo as a sample. The research instrument in the form of a SPS test sheet that was validated in terms of content and reliability, was given before (pretest) and after (posttest) the CPS learning intervention for 4 meetings. Data were analyzed using the N-Gain test to measure the increase in scores. The results of the analysis showed an N-Gain value of 0.80, which is classified as high. These findings indicate that the CPS model has succeeded in stimulating students' active participation in identifying problems, formulating hypotheses, and testing solutions through structured experiments. Significant improvements were especially seen in the aspects of designing investigations and interpreting data. The implications of the study confirm that the integration of the CPS model in science learning is not only effective in improving KPS, but also in building critical and collaborative thinking patterns. Thus, this model is worthy of consideration as an innovative alternative to strengthen students' scientific literacy at the elementary education level. ABSTRAKKeterampilan Proses Sains (KPS) merupakan kompetensi fundamental yang memungkinkan siswa menerapkan metode ilmiah untuk mengeksplorasi fenomena sains secara sistematis. Pengembangan KPS tidak hanya mendorong pemahaman konseptual, tetapi juga melatih kemampuan observasi, analisis, dan pemecahan masalah. Penelitian ini bertujuan menguji efektivitas model pembelajaran Creative Problem Solving (CPS) dalam meningkatkan KPS siswa kelas VIII. Metode yang digunakan adalah pre-experimental design dengan rancangan one-group pretest-posttest, melibatkan 27 peserta didik kelas VIII-B di sebuah SMP di Sidoarjo sebagai sampel. Instrumen penelitian berupa lembar tes KPS yang divalidasi secara konten dan reliabilitas, diberikan sebelum (pretest) dan setelah (posttest) intervensi pembelajaran CPS selama 4 pertemuan. Data dianalisis menggunakan uji N-Gain untuk mengukur peningkatan skor. Hasil analisis menunjukkan nilai N-Gain sebesar 0,80, yang tergolong dalam kategori tinggi. Temuan ini mengindikasikan bahwa model CPS berhasil menstimulasi partisipasi aktif siswa dalam mengidentifikasi masalah, merumuskan hipotesis, dan menguji solusi melalui eksperimen terstruktur. Peningkatan signifikan terutama terlihat pada aspek merancang investigasi dan menginterpretasi data. Implikasi penelitian menegaskan bahwa integrasi model CPS dalam pembelajaran sains tidak hanya efektif meningkatkan KPS, tetapi juga membangun pola pikir kritis dan kolaboratif. Dengan demikian, model ini layak dipertimbangkan sebagai alternatif inovatif untuk memperkuat literasi sains siswa di tingkat pendidikan dasar.